Tumor cellularity beyond the visible in soft tissue sarcomas: Results of an ADC-based, single center, and preliminary radiomics study - Giraudo, Chiara; Fichera, Giulia; Del Fiore, Paolo; Mocellin, Simone; Brunello, Antonella; Rastrelli, Marco; Stramare, Roberto (Frontiers in Oncology, 2022)
Abstract Purpose: Soft tissue sarcomas represent around 1% of all malignancies and diagnostic radiology plays a significant role in the overall management of this rare group of tumors. Recently, quantitative imaging and in particular radiomics demonstrated to provide significant novel information, for instance, in terms of prognosis and grading. Aim of this study was to use evaluate the prognostic role of radiomic variables extracted from ADC maps collected at diagnosis in patients with soft tissue sarcomas in terms of overall survival and metastatic spread as well as to assess the relationship between radiomics and tumor grade. Methods: Patients with histologically proven soft tissue sarcomas treated in our tertiary center from 2016 to 2019 who underwent an MR scan at diagnosis including DWI were included in this retrospective institution review board approved study. Each primary lesion was segmented using the b50 images; the volumetric region of interest was then applied on the ADC map. Thirty-three radiomic features were extracted and high correlating features selected by factor analysis. In case of feature/s showing statistically significant results, the diagnostic accuracy was computed. The Spearman correlation coefficient was used to evaluate the relationship between tumor grade and radiomic features selected by factor analysis. All analyses were performed applying p<0.05 as significant level. Results: Thirty-six patients matched the inclusion criteria (15 females; mean age 58.9 ± 15 years old). The most frequent histotype was myxofibrosarcoma (16.6%) and most of the patients were affected by high grade lesions (77.7%). Seven patients had pulmonary metastases and altogether eight deceased. Only the feature Imc1 turned out to be a predictor of metastatic spread (p=0.045 after Bonferroni correction) with 76.7% accuracy. The value -0.16 showed 73.3% sensitivity and 71.4% specificity and patients with metastases showed lower values (mean Imc1 of metastatic patients -0.31). None of the examined variables was a predictor of the overall outcome (p>0.05, each). A moderate statistically significant correlation emerged only between Imc1 and tumors grade (r=0.457, p=0.005). Conclusions: In conclusion, the radiomic feature Imc1 acts as predictor of metastatic spread in patients with soft tissue sarcomas and correlates with tumor grade.